1970
DOI: 10.1111/j.1439-0507.1970.tb01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic paronychia, and oral and vaginal candidal carriage

Abstract: Summary In 60 patients with chronic paronychia, Candida was found in the paronychia in 39 patients (C. albicans in 30 of them), in the vagina in 8 patients (C. albicans in 7 of them) and in the mouths in 47 patients (C. albicans in 40 of them). In the mouths of a control group of 60 female patients of comparable age, Candida was found in only 30 (C. albicans in 24). The incidence of Candida in the mouth was not affected by the presence of “predisposing factors” nor was there any difference in candidal carriage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…[14][15][16] Whittle et al reported average duration of paronychia was 20 years, the longest being 35 years. 12 In present study the minimum length was 15 days while, longest duration was one year. respectively and they all agreed that candida albicans was the major pathogen.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…[14][15][16] Whittle et al reported average duration of paronychia was 20 years, the longest being 35 years. 12 In present study the minimum length was 15 days while, longest duration was one year. respectively and they all agreed that candida albicans was the major pathogen.…”
Section: Discussionmentioning
confidence: 45%
“…10 Hellier and Whittle et al found 77% and 72% incidence respectively in the above age groups. 11,12 In present study most of the patients were between 45-60 years of age group because of their devotions in religious activities.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Am haufigsten verbreitet sind Candida-Mykosen, diedurch die Ernahrungswege und die Vielfalt der medikamentosen Therapien begimstigt (13) zu Schleimhautinfektionen auch im Magendarmbereich fiihren. Systemische und lokale Hefe-Infektionen stehen zwischen Mutter und Kind in einer Wechselbeziehung (4,7).…”
Section: Introductionunclassified